Pitch volume and glenohumeral and hip motion and strength in youth baseball pitchers - Harding, J. L.; Picha, K. J.; Huxel Bliven, K. C. (Journal of Athletic Training, 2018)
Context: Increased pitch volume and altered glenohumeral (GH) and hip range of motion (ROM) and strength contribute to injury risk in baseball pitchers. Although these factors affect one another, whether they are related is unknown.